2014
DOI: 10.1128/mcb.01524-13
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor GATA1 Is Dispensable for Mast Cell Differentiation in Adult Mice

Abstract: Although previous studies have shown that GATA1 is required for mast cell differentiation, the effects of the complete ablation of GATA1 in mast cells have not been examined. Using conditional Gata1 knockout mice (Gata1(-/y)), we demonstrate here that the complete ablation of GATA1 has a minimal effect on the number and distribution of peripheral tissue mast cells in adult mice. The Gata1(-/y) bone marrow cells were capable of differentiating into mast cells ex vivo. Microarray analyses showed that the repress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 67 publications
6
33
0
Order By: Relevance
“…As reported previously, 4 the fraction of DP cells was decreased over time to only 7.9 6 1.5% of the initial amount on day 9 ( Figure 1A). Phase-contrast photomicrographs of the BMMCs on day 10 showed that the DCF/DCF BMMCs were irregular in size and shape compared with the CreER T2 control BMMCs ( Figure 1B).…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations
“…As reported previously, 4 the fraction of DP cells was decreased over time to only 7.9 6 1.5% of the initial amount on day 9 ( Figure 1A). Phase-contrast photomicrographs of the BMMCs on day 10 showed that the DCF/DCF BMMCs were irregular in size and shape compared with the CreER T2 control BMMCs ( Figure 1B).…”
Section: Resultssupporting
confidence: 59%
“…[5][6][7] Interestingly, however, inducible deletion of GATA2 DNA-binding domain C-finger (CF) in BMMCs resulted in a significant reduction in the number of the c-Kit/ FceRIa double-positive (DP) cells, whereas the deletion of GATA1 did not significantly affect the frequency of DP cells or the cell morphology or viability. 4 These results suggest that GATA2 plays a more important role than GATA1 for maintaining the mast cell identity in BMMCs. In addition to GATA1 and GATA2, several other transcription factors including microphthalmia-associated transcription factor (MITF), runt related transcription factor 1 (RUNX1), T cell acute lymphocytic leukemia 1, and spleen focus forming virus (SFFV) proviral integration oncogene (PU.1) have been demonstrated to be involved in mast cell development.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…1 Using tissue-specific knockouts, GATA1 expression is necessary for the development of eosinophils and basophils but not mast cells. [10][11][12] In humans, germline mutations of GATA1, although rare, can result in varying degrees of anemia and thrombocytopenia. For instance, in X-linked dyserythropoietic anemia and thrombocytopenia, heterozygous mutation of GATA1 p.V205M abrogates the interaction with friend of GATA protein 1 (FOG1), resulting in anemia and thrombocytopenia with aberrant morphology of the platelets.…”
mentioning
confidence: 99%